Fibrin Clots Maintain the Viability and Proliferative Capacity of Human Mesenchymal Stem Cells: An In Vitro Study. Issue 3 (March 2020) - Warth, Ryan J.; Shupe, Paul G.; Gao, Xueqin; Syed, Mohammad; Lowe, Walter R.; Huard, Johnny; Harner, Christopher D.
Abstract: Background: Augmentation of soft-tissue repairs with an autologous fibrin clot has been used clinically for nearly four decades; however, fibrin clots tend to produce an abundance of scar tissue, which is known to inhibit soft-tissue regeneration. Mesenchymal stem cells (MSCs) embedded in fibrin clots before repair could reduce scar tissue deposition and facilitate soft-tissue regeneration. To our knowledge, no published studies have directly evaluated the viability or bioactivity of MSCs in fresh human fibrin clots over time. The purpose of this study was to evaluate the viability and bioactivity of human MSCs inside human fibrin clots over time in nutritive and non-nutritive culture media. Questions/purposes: We hypothesized that human MSCs would (1) be captured inside fibrin clots and retain their proliferative capacity, (2) remain viable for at least 7 days in the fibrin clots, (3) maintain their proliferative capacity for at least 7 days in the fibrin clots without evidence of active apoptosis, and (4) display similar viability and proliferative capacity when cultured in a non-nutritive medium over the same time periods. Methods: Twelve patients (mean age 33.7 years; range 4-72 years) who underwent elective knee surgery were approached between February 2016 and October 2017; all patients agreed to participate and were enrolled. MSCs isolated from human skeletal muscle and banked after prior studies were used for this analysis. On the day of surgery and after expansion of the MSC population, 3-mL aliquots of phosphate-buffered saline containing approximately 600, 000 labeled with anti-green fluorescent protein (GFP) antibodies were transported to the operating room, mixed in 30 mL of venous blood from each enrolled patient, and stirred at 95 rpm for 10 minutes to create MSC-embedded fibrin clots. The fibrin clots were transported to the laboratory with their residual blood for analysis. Eleven samples were analyzed after exclusion of one sample because of a processing error. MSC capture was qualitatively demonstrated by enzymatically digesting half of each clot specimen, thus releasing GFP-positive MSCs into culture. The released MSCs were allowed to culture for 7 days. Manual counting of GFP-positive MSCs was performed at 2, 3, 4, and 7 days using an inverted microscope at 100 x magnification to document the change in the number of GFP-positive MSCs over time. The intact remaining half of each clot specimen was immediately placed in proliferation media and allowed to culture for 7 days. On Days 1, 2, 3, 4, and 7, a small portion of the clot was excised, flash-frozen, cryosectioned (8-μm thickness), and immunostained with antibodies specific to GFP, Ki67 (indicative of active proliferation), and cleaved caspase-3 ([CC3]; indicative of active apoptosis). Using an inverted microscope, we obtained MSC cell counts manually at time zero and after 1, 2, 3, 4, and 7 days of culture. Intact fresh clot specimens were immediately divided in half; one half was placed in nutritive (proliferation media) and the other was placed in non-nutritive (saline) media for 1, 2, 3, 4, and 7 days. At each timepoint, specimens were processed in an identical manner as described above, and a portion of each clot specimen was excised, immediately flash-frozen with liquid nitrogen, cryosectioned (8-μm thickness), and visualized at 200 x using an inverted microscope. The numbers of stain-positive MSCs per field of view, per culture condition, per timepoint, and per antibody stain type were counted manually for a quantitative analysis. Raw data were statistically compared using t-tests, and time-based correlations were assessed using Pearson's correlation coefficients. Two-tailed p values of less than 0.05 (assuming unequal variance) were considered statistically significant. Results: Green fluorescence, indicative of viable GFP-positive MSCs, was absent in all residual blood samples after 48 hours of culturing; GFP-positive MSCs were visualized after enzymatic digestion of clot matrices. The number of GFP-positive MSCs per field of view increased between the 2-day and 7-day timepoints (mean 5.4 ± 1.5; 95% confidence interval, 4.7-6.1 versus mean 17.0 ± 13.6; 95% CI, 10.4-23.5, respectively; p = 0.029). Viable GFP-positive MSCs were present in each clot cryosection at each timepoint up to 7 days of culturing (mean 6.2 ± 4.3; 95% CI, 5.8-6.6). There were no differences in MSC counts between any of the timepoints. There was no visible evidence of GFP +/CC3 + double-positive MSCs. Combining all timepoints, there were 0.34 ± 0.70 (95% CI, 0.25-0.43) GFP+/Ki67+ double-positive MSCs per field of view. The mitotic indices at time zero and Day 7 were 7.5% ± 13.4% (95% CI, 3.0%-12.0%) and 7.2% ± 14.3% (95% CI, 3.3%-12, 1%), respectively (p = 0.923). There was no visible evidence of GFP +/CC3 + double-positive MSCs (active apoptosis) at any timepoint. For active proliferation in saline-cultured fibrin clots, we found averages of 0.1 ± 0.3 (95% CI, 0.0-0.2) and 0.4 ± 0.9 (95% CI, 0.0-0.8) GFP/Ki67 double-positive MSCs at time zero and Day 7, respectively (p = 0.499). The mitotic indices in saline culture at time zero and Day 7 were 2.9% ± 8.4% (95% CI, 0.0%-5.8%) and 9.1% ± 20.7% (95% CI, 1.2%-17.0%; p = 0.144). There was no visible evidence of GFP +/CC3 + double-positive MSCs (active apoptosis) at any timepoint in either culturing condition. Conclusion: These preliminary in vitro results show that human MSCs mixed in unclotted fresh human venous blood were nearly completely captured in fibrin clots and that seeded MSCs were capable of maintaining their viability, proliferation capacity, and osteogenic differentiation capacity in the fibrin clot for up to 7 days, independent of external sources of nutrition. Clinical Relevance: Fresh human fibrin clots have been used clinically for more than 30 years to improve soft-tissue healing, albeit with scar tissue. Our results demonstrate that allogenic human MSCs, which reduce soft-tissue scarring, can be captured and remain active inside human fibrin clots, even in the absence a nutritive culture medium.